2010
DOI: 10.1007/s10530-010-9733-8
|View full text |Cite
|
Sign up to set email alerts
|

Eating their way to the top? Mechanisms underlying the success of invasive insect generalist predators

Abstract: Insect generalist predators have been introduced outside of their native range intentionally to improve biological control, or accidentally during commerce, and can subsequently become invasive. Invasive insect generalist predators (IIGP) have widespread impacts on invaded communities because they consume both herbivores and other predators. Also, they often reach higher densities than and displace similar native species. Reflecting the complexity of their ecological roles, a wide variety of mechanisms might c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 148 publications
(208 reference statements)
2
93
1
Order By: Relevance
“…Depending on local environmental settings and management practices, however, the addition of new predators into natural and managed ecosystems may further reduce herbivore populations or it may reduce overall benefit to primary producers by increasing competition and intraguild predation (e.g. Eubanks 2001;Snyder and Evans 2006;Bruno and Cardinale 2008;Crowder and Snyder 2010). The historic and successful intentional release of Monomorium pharaonis (Linnaeus, 1758) against bed bugs (Cimex lectularius Linnaeus, 1758) (Hemiptera: Cimicidae) in British army barracks in Gibraltar can be mentioned as a curiosity here (Jameson 1932).…”
Section: )mentioning
confidence: 99%
“…Depending on local environmental settings and management practices, however, the addition of new predators into natural and managed ecosystems may further reduce herbivore populations or it may reduce overall benefit to primary producers by increasing competition and intraguild predation (e.g. Eubanks 2001;Snyder and Evans 2006;Bruno and Cardinale 2008;Crowder and Snyder 2010). The historic and successful intentional release of Monomorium pharaonis (Linnaeus, 1758) against bed bugs (Cimex lectularius Linnaeus, 1758) (Hemiptera: Cimicidae) in British army barracks in Gibraltar can be mentioned as a curiosity here (Jameson 1932).…”
Section: )mentioning
confidence: 99%
“…This work yields two important general predictions: (i) invasion success of species feeding at multiple trophic levels should be higher, and (ii) their invasion speeds faster, than for introduced species feeding only on lower trophic levels. Prediction (i) is supported by recent theoretical and empirical studies [15,16]. Anecdotal evidence exists for prediction (ii); for example, estimated spread rates for the harlequin ladybird in Britain (58 -144.5 km yr 21 [7]) are an order of magnitude higher than those of another notorious invader, the grey squirrel (7.66 km yr 21 [12]).…”
Section: Discussionmentioning
confidence: 72%
“…Beetles have caused many issues regarding invasion, by outcompeting with native species for resources and destroying local flora (Crowder and Snyder 2010). Some prominent examples include the Colorado potato beetle and the Asian long-horned beetle.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, breeding patterns and diet are traits that would be interesting to compare to wings and body size to better create a profile of what types of beetles are successful on green roofs. In one study on feeding habits, the researchers found that the type of predation, generalist or specific, plays a role in successful colonization (Crowder and Snyder 2010). Dispersal is also affected by season and stability of the habitat, which are factors that may differ between green roofs and ground environments (Boivin & Hance 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation